K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

10 tháng 10 2019

\(x^4+2\)

\(=x^4+2x^2+1-\left(2x^2-1\right)\)

\(=\left(x^2+1\right)^2-\sqrt{2x^2-1}^2\)

\(=\left(x^2+1-\sqrt{2x^2-1}\right)\left(x^2+1+\sqrt{2x^2-1}\right)\)

10 tháng 10 2019

\(x^4+2\)

\(=x^4+4x^2+2-4x^2\)

\(=\left(x^2+2\right)^2-4x^2\)

\(=\left(x^2+2-2x\right)\left(x^2+2+2x\right)\)

\(=\left(x-1\right)^2\left(x+1\right)^2\)

13 tháng 12 2016

\(x^4+x^3+2x^2+x+1\)

\(=\left(x^4+2x^2+1\right)+\left(x^3+x\right)\)

\(=\left(x^2+1\right)^2+x\left(x^2+1\right)\)

\(=\left(x^2+1\right)\left(x^2+1+x\right)\)

13 tháng 12 2016

x^4+x^3+2x^2+x+1

=(x^4+2x^2+1)+(x^3+x)

=(x^2+1)^2+x(x^2+1)

=(x^2+1)(x^2+x+1)

6 tháng 11 2016

x2-y2+6x+6y = (x2-y2)+(6x+6y) = (x-y)(x+y)+6(x+y) = (x-y-6)(x+y)

26 tháng 10 2018

\(x^2-4x+3\)

\(=x^2-x-3x+3\)

\(=x\left(x-1\right)-3\left(x-1\right)\)

\(=\left(x-1\right)\left(x-3\right)\)

26 tháng 10 2018

x2-4x+3

=x.x-x-3x-3

=x.(x-1)-3.(x-1)

=(x-1)(x-3)

4 tháng 1 2019

\(A=\left(x+1\right)\left(x-4\right)\left(x+2\right)\left(x-8\right)+4x^2\)

\(A=\left[\left(x+1\right)\left(x-8\right)\right]\left[\left(x-4\right)\left(x+2\right)\right]+4x^2\)

\(A=\left(x^2-7x-8\right)\left(x^2-2x-8\right)+4x^2\)

Đặt \(p=x^2-4,5x-8\)ta có :

\(A=\left(p-2,5x\right)\left(p+2,5x\right)+4x^2\)

\(A=p^2-\left(2,5x\right)^2+4x^2\)

\(A=p^2-6,25x^2+4x^2\)

\(A=p^2-2,25x^2\)

\(A=p^2-\left(1,5x\right)^2\)

\(A=\left(p-1,5x\right)\left(p+1,5x\right)\)

Thay \(p=x^2-4,5x-8\)vào A ta có :

\(A=\left(x^2-4,5x-8-1,5x\right)\left(x^2-4,5x-8+1,5x\right)\)

\(A=\left(x^2-6x-8\right)\left(x^2-3x-8\right)\)

4 tháng 1 2019

\(\left(x+1\right)\left(x-4\right)\left(x+2\right)\left(x-8\right)+4x^2\)

\(=\left(x+1\right)\left(x-8\right)\left(x-4\right)\left(x+2\right)+4x^2\)

\(=\left(x^2-7x-8\right)\left(x^2-2x-8\right)+4x^2\)

  Đặt \(x^2-2x-8=t\)

  Ta có : \(\left(t-5x\right)t+4x^2\)

\(=t^2-5xt+4x^2\)

\(=t^2-2.\frac{5}{2}xt+\frac{25}{4}x^2-\frac{9}{4}x^2\)

\(=\left(t-\frac{5}{2}\right)^2-\frac{9}{4}x^2\)

\(=\left(t-\frac{5}{2}-\frac{3}{2}x\right)\left(t-\frac{5}{2}+\frac{3}{2}x\right)\)

    Học tốt ~~

30 tháng 10 2018

\(5x^2-x+y-5y^2\)

\(=\left(5x^2-5y^2\right)-\left(x-y\right)\)

\(=5\left(x^2-y^2\right)-\left(x-y\right)\)

\(=5\left(x-y\right)\left(x+y\right)-\left(x-y\right)\)

\(=\left(x-y\right)\left[5\left(x+y\right)-1\right]\)

\(=\left(x-y\right)\left(5x+5y-1\right)\)

4 tháng 12 2019

\(x^4+x^2y^2+y^4\)

\(=x^4+2x^2y^2+y^4-x^2y^2\)

\(=\left(x^2+y^2\right)^2-\left(xy\right)^2\)

\(=\left(x^2+y^2-xy\right)\left(x^2+y^2+xy\right)\)

24 tháng 8 2019

\(4\left(x+3y-4\right)^2-x^2+6x-9\)

\(=\left[2\left(x+3y-4\right)\right]^2-\left(x^2-6x+9\right)\)

\(=\left[2x+6y-8\right]^2-\left(x-3\right)^2\)

\(=\left(2x+6y-8+x-3\right)\left(2x+6y-8-x+3\right)\)

\(=\left(3x+6y-11\right)\left(x+6y-5\right)\)

24 tháng 10 2018

\(=6x^2+9x+4x+6\)

\(=3x.\left(2x+3\right)+2.\left(2x+3\right)\)

\(=\left(2x+3\right).\left(3x+2\right)\)

\(\)

24 tháng 10 2018

6x2 + 13x + 6

= 2x(3x + 2) + 3(3x + 2)

= (3x + 2)(2x + 3)

31 tháng 10 2016

(2x2 - 4)2 + 9 = 4x4 - 16x2 + 25

= (4x4 + 20x2 + 25) - 36x2 = (2x2 + 5)2 - 36x2 

= (2x2 - 6x + 5)(2x2 + 6x + 5)

30 tháng 10 2016

(2x2-4)2+9

=(2x2-4)2+32

=(2x2 - 4+3)(2x2-4-3)

=(2x2 - 7)(2x2 - 1)

Tích cho mk nha!

23 tháng 9 2018

ab(x2+y2)+xy(a2+b2)

\(=abx^2+aby^2+a^2xy+b^2xy=\left(abx^2+a^2xy\right)+\left(aby^2+b^2xy\right).\)

\(=ax\left(bx+ay\right)+by\left(ay+bx\right)=\left(ax+by\right).\left(ay+bx\right)\)